2022
DOI: 10.3389/fped.2022.966237
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of pediatric tuberculosis in eastern Ethiopia

Abstract: BackgroundChildren are more vulnerable to developing active Mycobacterium tuberculosis infection which causes significant morbidity and mortality. However, the contribution of childhood tuberculosis and its treatment outcomes have not been well documented, and no research has been conducted in eastern Ethiopia.ObjectiveThis study aimed to assess the treatment outcome and its predictors of pediatric tuberculosis in eastern Ethiopia from September 1, 2017 to January 30, 2018.MethodsA retrospective study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
1
Order By: Relevance
“…Our study’s death rate (5.6%; 95% CI = 4.0–7.7%) is significantly higher than that of an earlier study in eastern Ethiopia (1.0%; 95% CI = 0.6–1.5) [ 21 ]. The eastern Ethiopia study did involve TB meningitis patients, which may explain the lower death rate observed in its findings, as TB meningitis has a 20% case fatality rate [ 38 ].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Our study’s death rate (5.6%; 95% CI = 4.0–7.7%) is significantly higher than that of an earlier study in eastern Ethiopia (1.0%; 95% CI = 0.6–1.5) [ 21 ]. The eastern Ethiopia study did involve TB meningitis patients, which may explain the lower death rate observed in its findings, as TB meningitis has a 20% case fatality rate [ 38 ].…”
Section: Discussioncontrasting
confidence: 82%
“…To reduce the death rate among children receiving TB treatment to the greatest extent possible, we must identify the predictors of death to implement risk factor-focused interventions in addition to anti-TB treatment [12][13][14]. Although it has been shown in other parts of the world that the Bacillus Calmette Guerin (BCG) vaccine is effective at preventing TB deaths in children [15] and under nutrition increases the risk of death from TB in adults [16,17], studies in Africa and Ethiopia [11,[18][19][20][21][22][23][24][25][26][27] left these factors out. The aim of this study was to describe the epidemiology of childhood TB and identify predictors of death in children with presumed drug-susceptible TB in central Ethiopia between 2014 and 2022.…”
Section: Introductionmentioning
confidence: 99%